GroEL is an immunodominant surface-exposed antigen of Rickettsia typhi - Rauch, Jessica; Barton, Jessica; Kwiatkowski, Marcel; Wunderlich, Malte; Steffen, Pascal; Moderzynski, Kristin; Papp, Stefanie; Höhn, Katharina; Schwanke, Hella; Witt, Susanne; Richardt, Ulricke; Mehlhoop, Ute; et al. (PLOS ONE, 2021)
Rickettsioses are neglected and emerging potentially fatal febrile diseases that are caused by obligate intracellular bacteria, rickettsiae. Rickettsia (R.) typhi and R. prowazekii constitute the typhus group (TG) of rickettsiae and are the causative agents of endemic and epidemic typhus, respectively. We recently generated a monoclonal antibody (BNI52) against R. typhi. Characterization of BNI52 revealed that it specifically recognizes TG rickettsiae but not the members of the spotted fever group (SFG) rickettsiae. We further show that BNI52 binds to protein fragments of ±30 kDa that are exposed on the bacterial surface and also present in the periplasmic space. These protein fragments apparently derive from the cytosolic GroEL protein of R. typhi and are also recognized by antibodies in the sera from patients and infected mice. Furthermore, BNI52 opsonizes the bacteria for the uptake by antigen presenting cells (APC), indicating a contribution of GroEL-specific antibodies to protective immunity. Finally, it is interesting that the GroEL protein belongs to 32 proteins that are differentially downregulated by R. typhi after passage through immunodeficient BALB/c CB17 SCID mice. This could be a hint that the rickettsia GroEL protein may have immunomodulatory properties as shown for the homologous protein from several other bacteria, too. Overall, the results of this study provide evidence that GroEL represents an immunodominant antigen of TG rickettsiae that is recognized by the humoral immune response against these pathogens and that may be interesting as a vaccine candidate. Apart from that, the BNI52 antibody represents a new tool for specific detection of TG rickettsiae in various diagnostic and experimental setups.